The Added Value of Internal Audit as a Third Line: A Case Study on Indonesia's Social Health Insurance Provider - Tandid Nasal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The assignment of the Health Social Security Program mandated to Indonesia's Social Health Insurance Provider (ISHP) is very crucial and faces many challenges. Various issues faced by ISHP often disrupt the stability of the Health Social Security program. The strategy's success and proper risk management will determine the program's sustainability. Therefore, the role of internal audit as a third line to ensure the effectiveness of strategic risk management is very important. This study uses a qualitative case study approach with three lines model of the IIA framework. This study evaluates the added value that internal audits can provide as a third line for supporting the success of social health insurance programs.